Integrative analysis identifies potential ferroptosis-related genes of hypoxia adaptation in yak - Zhang, Jian; Cui, Yan (Frontiers in Veterinary Science, 2022)
Yaks can adapt to high-altitude hypoxia environment, but there are few studies on the regulation of cell death by hypoxia. Recent research suggests a new type of programming cell death-ferroptosis is regulated by hypoxia. Therefore, this study was the first time to study ferroptosis-related genes about hypoxia in yak. In this study, the oviduct epithelial cells between yak and bovine are performed by integrative analysis for functions, regulating network and hub genes. The results showed 29 up-regulated ferroptosis genes and 67 down-regulated ferroptosis genes, GO-KEGG analysis showed that up-regulated DEGs were significantly enriched in ribosome pathway and oxidative phosphorylation pathway. Down-regulated differentially expressed genes(DEGs) were is significantly enriched in longevity regulating pathway-mammal pathway. Mitophagy-Animal Pathway was a significant enrichment pathway for the up-regulated differentially expressed ferroptosis genes(DE-FRGs). HIF-1 signaling pathway is a significant pathway for the down-regulated DE-FRGs. By constructing DE-FRGs protein-protein interaction (PPI) network, 10 hub DE-FRGs (Jun, STAT3, SP1, HIF1A, Mapk1, Mapk3, Rela, CDKN1A, EPAS1). The bta-mir-21-5p, bta-mir-10a and bta-mir-17-5p related to STAT3 were predicted. The results of this study excavated the important genes and pathways of the hypoxia in yak, and it was the first time for ferroptosis genes and pathways related to the hypoxia adaptation. This study provided sufficient transcriptome datas for hypoxia adaptation.